Facile Synthesis of Silanols via Cesium Carbonate Catalyzed Hydrosilanes with Water - Bai, Yunfeng; Chai, Miaomiao; Ma, Cong; Han, Zhengang (Synthesis, 2024)
The demand for green and efficient methods for preparing silanols is significant. In this study, we employed inexpensive cesium carbonate as a catalyst to facilitate the hydrolysis of hydrosilanes for silanol production. This approach offers numerous advantages, including mild reaction conditions, broad substrate compatibility, straightforward post-treatment procedures, high yields, and scalability to gram-level synthesis. Our method demonstrated compatibility with diverse organosilanes bearing alkyl, aryl, alkynyl, and heterocyclic substituents, including sterically hindered variants. The significance of these findings extends beyond scientific inquiry, offering practical utility in the synthesis of silanols.
Keywords: silanes; silanols; synthetic methods; cesium carbonate; catalyzer